(untitled) (Research, Society and Development, 2022)
Objective: To report the profile of patients with Inflammatory Bowel Disease followed up at a pediatric gastroenterology service in Brazil Northeast. Methodology: Series of cases through the active search of medical records from April to November 2020, with inclusion criteria the regular follow-up at the Gastropediatrics service and non-inclusion criteria the incomplete medical records (without clinical, laboratory, endoscopic and/or histopathological criteria of Inflammatory Bowel Disease), with a final sample of 22 participants. Results: Most were male (63.6%), had Ulcerative Colitis (59.1%) and came from the capital (63.6%). The main symptoms were: diarrhea with blood (63.6%), abdominal pain (27.3%) and diarrhea without blood (9%). Fecal Calprotectin was elevated (88.9%) and anemia was present (77.3%). Most were eutrophic (59.1%). Corticosteroids (72.7%) and Mesalazine (27.3%) were used in the remission phase, while Azathioprine (18.2%) and immunobiologicals (36.6%) in the follow-up. Conclusion: More studies on this topic are still expected, as well as trained professionals and effective health services are needed to receive precociously and to forward in long-term these patients to improve their quality of life and impact positively of the disease’s evolution.